The effect of blur on visual selective attention - Peterson, Jared (Kansas State University, 2016)
The effect of blur/clarity contrast on selective attention was investigated in terms of how unique blur and/or clarity guides attention. Visual blur has previously been suggested to be processed preattentively using a dual-task paradigm (Loschky et al., 2014). Experiments 1 and 2 used rotated L and T visual search tasks with blur/clarity contrast being manipulated such that it was non-predictive of the target’s location. Each experiment was preceded by a legibility control study such that blurred and clear letters had similar accuracy and reaction times. This allowed for the results to be interpreted as changes in attention rather than difficulty identifying the letters because they were blurry. Results suggest that when non-predictive of target location, unique blur plays a passive role in selective attention in which it is ignored, neither capturing nor repelling attention to its spatial location, whereas unique clarity captures attention. The findings provide insight to the role that blur/clarity contrast plays in guiding visual attention, which can be implemented in visual software to help guide selective attention to critical regions of interest displayed on a computer screen.
Keywords: Vision; Selective Attention; Visual Blur; Visual Search